SOCIAL VALUES OF THE CHARACTERS IN THE MOVIE “ME BEFORE YOU” - Dour, Maria Novia (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2024)
Watching movies is now a daily life for some people, even a hobby. Sometimes people just watch and forget some important things that we can take from the film. One of them is social value that we can use as an example to deal with various life problems, that is the purpose of this paper. Social value are made synonymous with need and neither the behavior not need of individuals are differentiated. This study focused on analyzed the social value in the movie of me before you. Social value not just found in the movie, conversation, but also it can found in our daily life. The method that the writer used is the descriptive qualitative method and before analyzed the data the writer used some steps in process of collecting the data it is watching the movie carefully and repeatdly, reading the script. The process of collecting the data. The process of collecting data was divided into three steps there are; watching and understanding the movie in several times, finding out the transcript, reading the script, the collected data. In analyzing the data, the writer used the theory purposed by S.Alisjahban (1974) in his book entitled Values as intergrating forces in Personality, Society and Culture and support by Halliday and Hassan (1985) as a context of situation. The result of this study show the total data that found in movie me before you are 40 data of social value it is 25 or 75% of Solidarity and 15 or 25% of power. Social value is the important aspect which is the respect of the one people to another people in community or our daily life. Watching movies is now a daily life for some people, even a hobby. Sometimes people just watch and forget some important things that we can take from the film. One of them is social value that we can use as an example to deal with various life problems, that is the purpose of this paper. Social value are made synonymous with need and neither the behavior not need of individuals are differentiated. This study focused on analyzed the social value in the movie of me before you. Social value not just found in the movie, conversation, but also it can found in our daily life. The method that the writer used is the descriptive qualitative method and before analyzed the data the writer used some steps in process of collecting the data it is watching the movie carefully and repeatdly, reading the script. The process of collecting the data. The process of collecting data was divided into three steps there are; watching and understanding the movie in several times, finding out the transcript, reading the script, the collected data. In analyzing the data, the writer used the theory purposed by S.Alisjahban (1974) in his book entitled Values as intergrating forces in Personality, Society and Culture and support by Halliday and Hassan (1985) as a context of situation. The result of this study show the total data that found in movie me before you are 40 data of social value it is 25 or 75% of Solidarity and 15 or 25% of power. Social value is the important aspect which is the respect of the one people to another people in community or our daily life.